Tin Oxide Based Nano Electroceramics Obtained from Sol-Gel Process: The Modified of the Structural and Opto-Electrical Properties with the Al Doping - Aydin, Cihat (Amer Scientific Publishers, 2018)
Nano electroceramic samples of undoped and Al doped SnO2 were synthesized by the sol-gel calcination process. The structural, morphological, electrical and optical properties of samples were characterized. X-ray diffraction analysis results confirm that all of the synthesized nanopowders are polycrystalline with a tetragonal structure. The crystallite size values of the prepared nanocomposites were calculated in the range of 21.32-34.33 nm. The values of crystallite size indicate that the prepared powders have nanostructure. The grain size and morphological parameters of the undoped and Al-doped SnO2 nanopowders calculated. AFM measurements suggest that Al dopants ratio could be an effect to control surface parameters of the SnO2 nanomaterials. The optical band gap (E-g) of prepared nanomaterials were calculated using Tauc plot method for the various atomic ratios of Al. The calculated Eg values for samples are found to be in the range from 3.51 to 3.69 eV. The electrical conductivity of undoped and Al doped Tin oxide nanopowders were carried out at the temperature range from 290 to 420 K. It demonstrates that the electrical conductivity at room temperature and the activation energy of samples increase with the Al doping. The obtained results suggest that the structural, morphological, optical and electrical properties of SnO2 based nanomaterials can be controlled and changed with Al content.
Keywords: Nano Electroceramic; Al Doped Tin Oxide; Morphological Parameters; Optical Band Gap; Activation Energy